Elais Guineensis (Palm) lignocellulosic biomass dissolution with aqueous ionic liquid for biofuel production / Intan Suhada Azmi … [et al.] - Azmi, Intan Suhada; Sulaiman, Siti Aishah; Rosli, Nur Ruzaini; Che Kamarludin, Siti Norsyarahah; Mohd Safaai, Nor Sharliza (Research Innovation Business Unit, 2014)
Researchers are focusing on the study of second generation bio fuel which is sourced from the woody biomass or known as lignocellulosic biomass. The rapidly increasing demand for energy and environmental threat and also the depletion of fossil fuels reserve have drawn significant attention among researchers to explore the lignocellulosic ethanol production as an attractive research area. Unreliable fuel supply in several countries encourages researchers to develop renewable and sustainable fuels. It is also an effort to produce an environmental friendly and safer fuel that can reduce carbon dioxide emissions that contribute to global warming. There are abundant sources of lignocellulosic biomass such as grass, wood, municipal solid waste, agricultural waste, urban waste and the other waste which have the potential as a sustainable source of bio fuel production. Cellulose, hemicellulose and lignin contribute to the major component of wood having mostly 40-45 % cellulose from wood’s dry weight. Lignin holds plant cell together creating wood network resulting in the difficulty of the dissolution of cellulose unless the lignin’s bond is broken down. In Malaysia, dissolution of cellulose from Elais Guineensis (palm) to produce bioethanol as future bio fuels is very promising since palm residues from palm industry are quite substiantial. Moreover, cellulose contents in palm waste or residues are relatively high for instance from palm trunk and palm frond. In order to fully utilize the lignocellulosic biomass by making cellulose accessible for hydrolysis there must be an efficient pre-treatment method for deconstruction of biomass. Pre-treatment of the lignocellulosic biomass for at the earlier stage before producing bioethanol is very important for practical cellulose conversion processes. The kinds of processes needed nowadays are called green technology based technique which is environmental friendly. There are various solvent applied to dissolve cellulose including various type of ionic liquid as well. Ionic liquid is a green solvent that is able to dissolve lignin polymer because of the strong hydrogen bond in which it’s destroying abilities for processing biopolymers is strong. Ionic liquid is typically composed of large organic cation and small inorganic cation. In addition, ionic liquid is capable of dissolving cellulose as indicated by some researchers recently. Previously, other method such as acid hydrolysis pre-treatment process cause many drawbacks due to their low rates of hydrolysis and extreme acidic conditions. Among all of the pre-treatment method broadly studied, ionic liquid applications have drawn growing attention for lignocellulosic biomass production. The dissolution process of lignocellulosic biomass with ionic liquids is at its better advantage due to the better dissolution as compared to by using organic or inorganic solvents. However, the major barrier in commercialising this recent approach is due to high current cost of ionic liquid. Therefore, an innovation by using aqueous ionic liquid during pre-treatment of lignocellulosic biomass was discovered. The pre-treatment process was done by shaking the palm trunk and palm frond with the aqueous ionic liquid using microtiter plate and the absorbance value is measure using micro plate reader. The before and after effects of the aqueous ionic liquid pre-treatment is studied by using Fourier Transform Infrared (FTIR). It is well known following the current trend that efficient use of llignocellulosic materials on a commercial scale can be realized to the benefit of the society particularly in maintaining the sustainable development of the environment. The green chemistry principle are adopted whereby the use of ionic liquid as environmentally preferable solvent to dissolve the bio renewable feedstock from lignocellulosic wastes.